Cancer mortality among leather tanners. Issue 7 (July 1986) - Edling, C; Kling, H; Flodin, U; Axelson, O
Abstract : Workers were studied at a tannery that operated from 1873 to 1960, once one of the biggest in Scandinavia. The results show a slight numerical increase of deaths from cancer of the stomach and a significant, threefold excess mortality from cancer of the pancreas. Even in view of critical questions about validity it seems likely that this excess might be related to exposure to chemicals in tannery work.